Seasonal meteorological factors influencing the annual flight cycle ofProstephanus truncatus (Coleoptera: Bostrichidae) and its predator Teretriosoma nigrescens (Coleoptera:Histeridae) in Benin - Borgemeister, C.; Meikle, W.G.; Scholz, D.; Adda, C.; Degbey, P.; Markham, R.H. (Cambridge University Press, 1997)
Investigations were carried out in southern Benin on the annual flight cycle and the effects of weather variables on the flight activity of Prostephanus truncatus (Horn) and its natural enemy, Teretriosoma nigrescens Lewis. Two seasonal peaks in flight activity of P. truncatus were observed, one between the end of December and the beginning of January and a second one between May and June. Teretriosoma nigrescens showed a single delayed peak in June, approximately six weeks after the major peak of P. truncatus. Flight activity of P. truncatus was only weakly associated with weather characteristics (standardized regression coefficient for mean daily temperature b = 0.18, t = 2.87, P < 0.05)), whereas for T. nigrescens it was associated with precipitation (standardized regression coefficient for accumulated rainfall during the trapping period b = 0.38, t = 4.76, P < 0.05). The possibility that one of the P. truncatus peaks was associated with dispersal from crowded maize stores and the other with the search for natural woody host plants is discussed.